Stress from Digital Work: Toward a Unified View of Digital Hindrance Stressors - Gimpel, Henner; Lanzl, Julia; Regal, Christian; Urbach, Nils; Becker, Julia; Tegtmeier, Patricia (Information Systems Research, 2025)
Digital technologies, although enhancing productivity and communication, also contribute to technostress at work. This study addresses the fragmentation in existing models of hindrance technostressors by proposing a unified hierarchical model of digital hindrance stressors tailored to contemporary digital work environments. The research synthesizes various existing models and uses a mixed-methods approach, including a qualitative prestudy and extensive surveys with more than 5,800 participants to identify and validate 12 first-order and 5 second-order digital hindrance stressors. The new model offers both detailed and streamlined measurement tools, enhancing its applicability in diverse organizational contexts. For practitioners and policymakers, this study provides a comprehensive framework to assess and mitigate the adverse impacts of digital stressors. The unified model allows organizations to understand specific stressors their employees face and implement targeted interventions to improve well-being and productivity. By using this model, occupational health professionals can better address the psychological and physical health implications of technostress. Moreover, the findings offer actionable insights for designing digital work environments that minimize stress and foster a healthier, more productive workforce. This research bridges the gap between theoretical technostress models and practical applications, guiding effective strategies for managing digital workplace stress.